Foreign Direct Investment and Service Sector Performance in a Developing Economy: Lessons from Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study analyzes how foreign direct investment (FDI) affected the output of Nigeria's service sector from 1980 to 2020. The study uses service sector output as the regresand, FDI as the major regressor, and exchange rate (EXR) and government spending (GEX) were used as check variables. The data were sourced from the CBN Statistical Bulletin 2020. The nature of the variables necessitated the use of ECM. Results from the short run ECM dynamic model reveals that service sector output responds positively to FDI. We observed that the lag value of service sector output was positive and significant, implying that service sector output responds to past service sector output positively in Nigeria. The ECM's one-period lag coefficient was negative and significant at 0.05, indicating that service sector output adjusts to changes in explanatory variables and its own lag within a year. The ECMt-1 corrects 17.3% of the disequilibrium between static and short-run dynamic models of Service Sector Output (SSO) within a year on average. The study found that the service sector plays a crucial role in this developing economy's economic growth and development. It is an essential macroeconomic sector that can improve the economy's overall performance and influence the flow and direction of income as well as the Balance of Payments (BOP) position. According to the findings, the study suggests that the government should uphold financial responsibility and allocate more funds towards building necessary infrastructure to support the service sector's growth. This will ultimately improve the overall performance of the Nigerian economy.